Effect of deforestation and introduction of exotic grasses as livestock forage on the population dynamics of the cattle tick Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) in northern Argentina - Nava, Santiago; Mastropaolo, Mariano; Guglielmone, Alberto; Mangold, Atilio Jose (2018)
The effect of deforestation and the introduction of exotic grasses on the population dynamics of Rhipicephalus (Boophilus) microplus in northern Argentina was analysed. Biological parameters that were measured included proportion of females ovipositing, pre-oviposition period, incubation period of eggs, proportion of egg clusters hatching, larval longevity and total non-parasitic period. No significant differences were observed in proportion of females ovipositing and in pre-oviposition period between forested and grassland areas. Regarding the other parameters, in the majority of the temporal series there were no significant differences. In the cases where differences with statistical significance were detected, they were not unidirectional. The replacement of native forest by grasses can potentially increase tick abundance not by the modification of microclimatic conditions, but by increasing the tick-host encounter rate due to a higher cattle density. The hypothesis that deforestation and introduction of exotic grasses affects the non-parasitic phase of R. microplus in northern Argentina was not supported.